Implementasi Ballast Water Management Di Pelabuhan Tanjung Emas Semarang : Strategi dan Model Pengelolaan - Apriyanto Budhi Wibowo; Hugi Cerlyawati (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
The discharge of ballast water by commercial vessels impacted on the development of non-native species and the spread of heavy metal. In this research, descriptive methodology was applied whose research sample was obtained by random sampling method. Questionnaire and interviews were employed as the data collection method. In order to identify the strategy, the data were then analyzed by using SWOT (Strength, Weakness, Opportunity, and Threat). The research was aimed to formulate the model and strategy in the implementation of BWM (Ballast Water Management). BWM had been analyzed and applied to determine an appropriate model for ballast water treatment. In this case, the Harbour Master and Port Authority Office of Tanjung Emas can possibly apply a defensive strategy. This strategy emphasizes on the improvement of Port State Control (PSC) and penalties. In order to maintain the vessel stability, container vessels, passanger vessels, and ro-ro vessels are recommended to apply freshwater within their ballast tanks. Moreover, a ballast water treatment facility has also been provided by the port administrator, Pelindo III, for bulk carrier vessels and tankers to discharge their ballast water.